Modeling the effects of plastic film mulching on irrigated maize yield and water use efficiency in sub-humid Northeast China - Yang, Liu; Haishun, Yang; Yanfeng, Li; Haijun, Yan; Jiusheng, Li (International Journal of Agricultural and Biological Engineering, 2017)
In sub-humid Northeast China, plastic film mulching (PFM) is increasingly used with drip irrigation system in maize (Zea mays L.) to cope with seasonal droughts and low temperatures during seedling stage. Although there were several studies showing the benefits of PFM on maize production in the region, quantification of the effects of PFM in sub-humid Northeast China are still lacking. Hybrid-Maize model has a special version that can not only simulate the effects of PFM on reduction of soil evaporation and rise of topsoil temperature, but also simulate the effects of PFM on crop development and other physiological processes. This paper reports how to verify the Hybrid-Maize model against observations and then applying the model to quantify effects of PFM on grain yield and water use efficiency (WUE) under irrigated scenarios. The Hybrid-Maize model was added the heating effects of PFM on rising surface-soil temperature and promoting subsequent crop development by establishing equations between surface-soil temperature and air temperature before V6 stage. A 3-year field experiment including maize growth and yield data measured at a drip-irrigated field in Heilongjiang Province was used to serve the model calibration. The simulated results indicated that the Hybrid-Maize model performed well in simulation of seasonal soil water storage and in-season aboveground dry matter in three years, but overestimated the leaf area index (LAI) for both treatments and underestimated the final aboveground dry matter at maturity for mulched treatments. Although the Hybrid-Maize model overestimated the grain yield and WUE, it did still reflect the effects of PFM on increasing grain yield and WUE during the three growing seasons. The average simulated grain yield and WUE for mulched treatments were 8% and 13% greater compared to non-mulched treatments using 30 years weather data, which were in agreement with observations that average grain yield and WUE was 11% and 14% increased by PFM, respectively. For evapotranspiration (ET), the average simulated ET for mulched treatments was 22 mm less than non-mulched treatments mainly due to less soil evaporation. For simulated irrigation requirements, at most 69 mm of irrigation water could be saved by PFM. In conclusion, PFM with drip irrigation could improve irrigated maize production in sub-humid Northeast China.Keywords: film mulch, maize yield, water use efficiency, Hybrid-Maize model, drip irrigation, Northeast ChinaDOI: 10.25165/j.ijabe.20171005.2799Citation: Liu Y, Yang H S, Li Y F, Yan H J, Li J S. Modeling the effects of plastic film mulching on irrigated maize yield and water use efficiency in sub-humid Northeast China. Int J Agric & Biol Eng, 2017; 10(5): 69–84.